1Rational design of a charge shunt: modification upon crystal facet engineering of semiconductor photocatalysts. Issue 56 (18th June 2015) - Feng, Wenhui; Weng, Sunxian; Zheng, Zuyang; Fang, Zhibin; Liu, Ping
Abstract : Another carrier-shunt is artificially bridged over different facets of a semiconductor, achieving the unique facet-driven charge dual-selectivity-channel separation during photocatalysis. Abstract : Another excellent carrier shunt is artificially bridged over different exposed facets of a semiconductor, to achieve a unique architecture with superior photoactivity, which is mainly attributed to the facet-driven charge dual-selectivity-channel separation mechanism. This novel concept may break new ground in the rational modification of crystal facet engineering of a semiconductor.